PROYEKSI KETERSEDIAAN AIR TAHUN 2036 TERHADAP SUMBER AIR JUNREJO PADA HIPAM KELURAHAN DADAPREJA KECAMATAN JUNREJO KOTA BATU - Sutikno Sutikno (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
With the goverment of the Batu city in 2014, budgeted used source to tandon, the following tandon temporary shelter who are in the way of Dr. Sutomo with a capacity of 72 meters cubic, be distributed to four a ham let which each hamlet have tub shelter wiht dimensions in accordance needs. Existing souarce possess the capacity dischange 24 liters/seconds, with survey the population of water users in 2014 until 2016. It is expected that population growth and capacity discharge there would be can satisfy the needs of water in keluarahan Dadaprejo up until the 2036